TOWARDS A SYSTEMATISED ENGLISH LANGUAGE TRAINING FOR BORDER GUARDS - Žukova, Marina (Border Security and Management, 2016)
Ability to communicate in English is one of the prior competences border guards are required to have in order to ensure qualitative border control and border checks on the state border. Being aware of the importance of knowledge of English for border guards in fulfilment service duties on regular basis the State Border Guard of Latvia tried and tries to find optimal solutions for organising English language training for its staff. The present paper is a summary of the results of research carried out with the aim to work out suggestions on the measures to be taken in order to provide the SBG officials with the possibility to acquire and maintain English language knowledge and skills required for qualitative fulfilment of service duties. In the course of the research the assessment of border guards’ level of knowledge of English and analysis of English language courses provided by the SBG to border guards was carried out.